(untitled) (Journal of Hama University, 2019)
The study showed that administration of IBD vaccine after ND vaccine was better to develop higher immunity response of NDV BD on level antibody of ND. The aim of this study was to determine the effect of Infectious Bursal disease live vaccines on efficacy of Immunity against live vaccine of Newcastle Disease in broiler chickens. Three groups of broiler chickens, of one-day old, 100 chicks each, were rearing till forty-two days of age. First group served as control was kept unvaccinated, second group was vaccinated with Newcastle disease at 7 days and Infectious Bursal disease at 14 days, and the third group was vaccinated with Infectious Bursal disease at 7 days and Newcastle disease at 10 days of age. blood samples were obtained from each group at 5-day interval until 42 days. The Antibody titter against NDV was measured by HI test. The results were showed that antibody response of Newcastle Disease Vaccine was better when ND vaccine administered before IBD vaccine, and the effect of IBD vaccine on antibody levels against ND vaccine was lower when IBD vaccine was administered at 14 days of age as compared to 7 days of chicken age. The study showed that administration of IBD vaccine after ND vaccine was better to develop higher immunity response of NDV BD on level antibody of ND.